2006
DOI: 10.1177/183693910603100107
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Concepts and Theories: Reflections for Practice for early Childhood Directors

Abstract: This paper proposes that effective leadership is a vital component in providing quality childcare services. It suggests that developing an enhanced understanding of effective leadership frameworks can be a starting point for a quality process and can forge a commitment to working towards excellence in early childhood centres, as well as be a tool for self-reflection. Theories of leadership are outlined for future preparation of leaders in a complex environment in which centres now operate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The directors’ outward focus on their teams, and the recognition by staff of the role their director played, underscores the importance of the facilitative role of leadership in quality ECEC. The emphasis that these directors placed on the contribution of their teams is consistent with other studies that have highlighted the effectiveness of distributed leadership in early childhood services (Heikka et al, 2013; Nupponen, 2006; Press, 2012; Siraj-Blatchford & Manni, 2006) and research that illuminates the director’s role in supporting staff agency (Siraj-Blatchford & Hallet, 2014).…”
Section: Provocations About ‘Quality’ Early Childhood Education and Caresupporting
confidence: 76%
“…The directors’ outward focus on their teams, and the recognition by staff of the role their director played, underscores the importance of the facilitative role of leadership in quality ECEC. The emphasis that these directors placed on the contribution of their teams is consistent with other studies that have highlighted the effectiveness of distributed leadership in early childhood services (Heikka et al, 2013; Nupponen, 2006; Press, 2012; Siraj-Blatchford & Manni, 2006) and research that illuminates the director’s role in supporting staff agency (Siraj-Blatchford & Hallet, 2014).…”
Section: Provocations About ‘Quality’ Early Childhood Education and Caresupporting
confidence: 76%
“…While some room leaders in this study articulated inclusive approaches as conducive to professional learning within their teams (Keay & Lloyd, 2011), others adopted authoritative, directive approaches, suggesting reliance on positional leadership authority and an emphasis on tasks (Muijs et al, 2010). Directive leadership styles may be linked to managerial concepts such as understandings of staff supervision, direction and time efficiency which may limit open exploration and participation by educators (Nupponen, 2006). Research has found that positional leaders have significant roles in creating inclusive organisational climates for participation (Robinson, 2009), and inclusive attitudes are needed to create space for those not in formal leadership positions to lead where they have specific expertise (Glatter, 2009).…”
Section: Professional Dialogue Networkmentioning
confidence: 88%
“…More problematic is the negative construing, and limited change in the construing of the influences of administrators. Leadership in ECEC settings is pivotal to the provision of quality education and care (Brownlee, Nailon & Tickle, 2010;Nupponen, 2006;Thornton, 2010). Recent ideas around pedagogical leadership, community of practice and distributed leadership highlight the interrelated role of leaders at all levels with respect to curriculum and pedagogy decision making (Clarkin-Phillips, 2011; Heikka & Waniganayake, 2011;Watson & Williams, 2011).…”
Section: Discussionmentioning
confidence: 99%